2020
DOI: 10.1080/24750263.2020.1810336
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the oxidative system in Chironomidae larvae with contrasting feeding strategies

Abstract: The aim of the present work was to compare the oxidative system in the fourth-instar larvae of four species of Diptera belonging to the family Chironomidae: Chironomus riparius, Paratanytarsus sp., Prodiamesa olivacea and Conchapelopia melanops. These species were selected based on their ecological and biological differences and were assessed in relation to their ecological and biological characteristics. The following parameters of oxidative stress were determined: the levels of total antioxidant capacity (TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 84 publications
1
0
0
1
Order By: Relevance
“…After being exposed to high doses of chemicals, some of the larvae die. Similar results indicated that the population of larval chironomids when exposed to a polluted environment, exhibits specific responses in the form of changes in larval behavior and morphology [15][16][17]. The effects of the pesticide as a pollutant also change the morphology and behavior of chironomus riparius larvae.…”
Section: Discussionsupporting
confidence: 54%
“…After being exposed to high doses of chemicals, some of the larvae die. Similar results indicated that the population of larval chironomids when exposed to a polluted environment, exhibits specific responses in the form of changes in larval behavior and morphology [15][16][17]. The effects of the pesticide as a pollutant also change the morphology and behavior of chironomus riparius larvae.…”
Section: Discussionsupporting
confidence: 54%
“…Table S1: Compilation of data regarding the relationships between cyanobacteria and benthic macroinvertebrates. References [ 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , …”
unclassified